To solve the equation \(-x + (-1) = 3x + (-5)\) using algebra tiles, we will start by simplifying and rearranging the equation.
-
Rewrite the equation: \[ -x - 1 = 3x - 5 \]
-
Next, we'll add \(x\) to both sides to get all terms involving \(x\) on one side: \[ -1 = 3x + x - 5 \] This simplifies to: \[ -1 = 4x - 5 \]
-
Now, add \(5\) to both sides: \[ -1 + 5 = 4x \] Thus: \[ 4 = 4x \]
-
Finally, divide both sides by \(4\): \[ x = 1 \]
So, the value of \(x\) is \(1\).
The correct answer is: \(x = 1\)